Concentration of plasma sialic acid in the offspring of one type II diabetic parent - Ismail, I.S.; Qvist, R.; Muniandy, S.; Zaini, A. (Medimond Inc., 2001)
Sialic acid, oral glucose and plasma lipids were determined in 70 control subjects (age range 20-60) and 150 individuals of (age range 20-60) who were offspring of one type 2 diabetic parent. The number of first degree relatives who had impaired glucose tolerance were 50. The total sialic acid concentration was significantly higher (p<0.05) in the first degree relatives when compared to the control subjects. However the total sialic acid concentration was significantly higher in the offspring with normal glucose tolerance than in those with impaired glucose tolerance. There was no significant difference in the lipids between the control subjects and the offspring with normal glucose tolerance But the total cholesterol and triglycerides were significantly higher in the offspring with impaired glucose tolerance when compared to the control subjects and the offspring with normal glucose tolerance. Our study shows that desialylation of the vascular endothelium is an early event that precedes the expression of impaired glucose tolerance or any lipid changes in asymptomatic offspring of one type2 diabetic parent